Optimalisasi Digital Entrepreneurship Melalui Pelatihan Digital Marketing bagi Siswa-Siswi SMA Swasta Sultan Agung Pematangsiantar - Halim, Fitria; Sherly, Sherly; Lie, Darwin; Supitriyani, Supitriyani; Sudirman, Acai (Universitas Nusantara PGRI Kediri, 2023)
The main purpose of this community service activity with the theme of Optimizing Digital Entrepreneurship Through Digital Marketing Training for Private High School Students Sultan Agung Pematangsiantarini is to provide additional knowledge about the importance of using and utilizing digital marketing for business management to gain competitive competitiveness. The method used to implement this activity is through lectures and direct practice of using and creating e-commerce accounts. The stages of implementing this service include the opening and introduction of digital entrepreneurship, exposure to the introduction of digital entrepreneurship and competitiveness, presenting some of the problems students often face regarding digital marketing, and then continued with practices related to e-commerce. After the service activities were completed, a follow-up interview was conducted regarding the impact of implementing the service activities. Following the results of follow-up interviews, it is known that the changes that occurred after participating in the activity, namely understanding of the digital aspect of entrepreneurship and understanding related to the use of digital marketing increased by 80%.